Historic time travel peek into industry & agriculture (A2ZCDS.com, 2004)
A tour de force video dating way back to 1920-60 depicts the encouragement provided to industrialization & the production of consumer goods and the implementation of latest technologies which allowed a spurt in agricultural growth in South American and the Philippines.